Reverse Logistics for Malaysian Tire Industry: A Conceptual Framework for Strategic Implementation - Rizad Md Sapry, Hairul; Shakina Mohamad Ridwan, Nurul; Rahman Ahmad, Abd; Baskaran, Shathees; ., . (International Journal of Engineering and Technology, 2018)
The deficiency in product performance of tire which concerns safety issue requires an immediate pull back from the market.Â An increasing trend of defect tires pull back from the market has made enforcement of environmental legislation to be more forceful and that is one of the reasons tire manufacturers scouting for possible distribution channels or methods to enhance reverse logistics as part of their supply chain.Â In order to provide a conceptual strategic implementation direction, this research adopted qualitative method occupying in-depth interviews with major tire manufacturing companies in Malaysia to extract the data and explore resulting themes. A strategic model of implementation of reverse logistics for tire industry in Malaysia has been established as a guide for academician, practitioners and relevant regulatory bodies with an aim to improve the process of reverse logistics addressing cost structure and environment issues as well as to introduce and enhance the possibility of reverse logistics in the supply chain of tire industry in Malaysia.Â